Analisis Preferensi Konsumen Buah Kiwi pada Hypermart di Kota Surabaya - Vanya Agita Sari; Teguh Soedarto; Prasmita Dian Wijayati (Jurnal Ilmiah Sosio Agribis, 2022)
This study examines the consumer preferences for kiwi fruit at Hypermart. The purpose of this study is to determine the characteristics of consumers of kiwi fruit, analyze the attributes of kiwi fruit that are considered by consumers, and analyze the level of consumer satisfaction when buying kiwi fruit at Hypermart. In this study, using the purposive sampling technique, we obtained as many as 50 respondents. The analysis used is descriptive analysis, Fishbein, and Likert scale analysis. The results of this study are: 1) The characteristics of kiwifruit consumers are dominated by women, aged 21–30 years; the latest education is a bachelor's degree (S1); they work as private employees with a monthly income of > 5,000,000. 2) The most important attribute to be considered by consumers is the taste attribute, and consumers give a positive attitude towards all attributes of kiwi fruit. In addition to the taste attribute, the other two attributes that are considered by consumers are benefits and nutritional content. 3) Consumers give very satisfied responses when shopping for kiwi fruit at Hypermart. Among the six elements of the proposed statement, the one most highly satisfied by consumers is the quality of the kiwi fruit at Hypermart.Keywords: Attributes, Characteristics, Consumer Preference, Consumer Satisfaction, Kiwi Fruit